Presentation - Xavier Baez, Narciso Leandro; Mozetic, Vinícius; Strapazzon, Carlos Luiz (Unoesc International Legal Seminar, 2017)
The INTERNATIONAL NETWORK OF HUMAN RIGHTS is an idea of joining Universities and scholars from around the world with similar interests on human rights and human dignity. It is mostly a mean to develop international cooperation in order to purpose solutions to human rights violations. On September 26-30, 2016 Universidade do Oeste de Santa Catarina (Brazil) hosted foreign and Brazilian scholars so as to address this challenging issue...